Single crystal growth, structure and magnetic properties of Pr2Hf2O7 pyrochlore. (29th December 2016) - Hatnean, Monica Ciomaga; Sibille, Romain; Lees, Martin R; Kenzelmann, Michel; Ban, Voraksmy; Pomjakushin, Vladimir; Balakrishnan, Geetha
Abstract: Large single crystals of pyrochlore P r 2 H f 2 O 7 were successfully grown by the floating zone technique using an optical furnace equipped with high power xenon arc lamps. Structural investigations were carried out via powder synchrotron x-ray and neutron diffraction to establish the crystallographic structure of the materials produced. The magnetic properties of the single crystals were determined for magnetic fields applied along different crystallographic axes. The results revealed that P r 2 H f 2 O 7 is an interesting material for further investigation as a frustrated magnet. The high quality of the crystals produced makes them ideal for detailed investigation, especially using neutron scattering techniques.